Thioredoxin 1 in Prostate Tissue Is Associated with Gleason Score, Erythrocyte Antioxidant Enzyme Activity, and Dietary Antioxidants - Terrence M. Vance; Gissou Azabdaftari; Elena A. Pop; Sang Gil Lee; L. Joseph Su; Elizabeth T. H. Fontham; Jeannette T. Bensen; Susan E. Steck; Lenore Arab; James L. Mohler; Ming-Hui Chen; Sung I. Koo; et al. (Prostate Cancer)
Background. Prostate cancer is the most common noncutaneous cancer and second leading cause of cancer-related mortality in men in the US. Growing evidence suggests that oxidative stress is involved in prostate cancer. Methods. In this study, thioredoxin 1 (Trx 1), an enzyme and subcellular indicator of redox status, was measured in prostate biopsy tissue from 55 men from the North Carolina-Louisiana Prostate Cancer Project. A pathologist blindly scored levels of Trx 1. The association between Trx 1 and the Gleason score, erythrocyte antioxidant enzyme activity, and dietary antioxidant intake was determined using Fisher’s exact test. Results. Trx 1 levels in benign prostate tissue in men with incident prostate cancer were positively associated with the Gleason score (P=0.01) and inversely associated with dietary antioxidant intake (P=0.03). In prostate cancer tissue, Trx 1 levels were associated with erythrocyte glutathione peroxidase activity (P=0.01). No association was found for other erythrocyte enzymes. Greater Gleason score of malignant tissue corresponds to a greater difference in Trx 1 levels between malignant and benign tissue (P=0.04). Conclusion. These results suggest that the redox status of prostate tissue is associated with prostate cancer grade and both endogenous and exogenous antioxidants.